Experiencing cardiac arrest during surgical exploration in hemodynamically stable patients with multiple stab wounds, including lower extremity in Korea: a case report - Jung Rae Cho; Dae Sung Ma (Daehan oe'sang haghoeji, 2024)
Stab wounds, particularly those affecting multiple body regions, present considerable challenges in trauma care. This report describes a case of sustained self-inflicted stab injuries to the abdomen and thighs of a 23-year-old male patient. Although the patient's vital signs were stable and bleeding was minimal from thigh wounds without overt signs of vascular injury, the patient experienced a sudden, profound hemorrhage from the right thigh, leading to cardiac arrest. Successful resuscitation was followed by surgical repair of a right superficial femoral arterial injury accompanying a resuscitative endovascular balloon of the aorta. Subsequent lower extremity computed tomography angiography revealed no additional vascular abnormalities. The patient was discharged in stable condition on the 12th postoperative day. This case underscores the unpredictability of stab wound trajectories and the potential for hidden vascular injuries, even in the absence of immediate life-threatening signs. It also emphasizes the critical role of advanced imaging modalities, such as computed tomography angiography, in identifying concealed injuries, and the importance of strategic intraoperative techniques, including resuscitative endovascular balloon occlusion of the aorta, in achieving favorable patient outcomes.